2015
DOI: 10.1038/srep08227
|View full text |Cite
|
Sign up to set email alerts
|

Co-overexpression of geraniol-10-hydroxylase and strictosidine synthase improves anti-cancer drug camptothecin accumulation in Ophiorrhiza pumila

Abstract: Camptothecin (CPT) belongs to a group of monoterpenoidindole alkaloids (TIAs) and its derivatives such as irinothecan and topothecan have been widely used worldwide for the treatment of cancer, giving rise to rapidly increasing market demands. Genes from Catharanthus roseus encoding strictosidine synthase (STR) and geraniol 10-hydroxylase (G10H), were separately and simultaneously introduced into Ophiorrhiza pumila hairy roots. Overexpression of individual G10H (G lines) significantly improved CPT production w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(56 citation statements)
references
References 35 publications
0
56
0
Order By: Relevance
“…There are a lot of successful cases in this field. In A. belladonna and A. acutangulus , biosynthesis of scopolamine was dramatically enhanced by overexpressing the committed enzymes, H6H and TRI in A. annua , the production of artemisinin was greatly promoted by overexpressing CYP71AV1 and aldehyde 11Δ(13) reductase ; in Catharanthus roseus , overexpressing strictosidine synthase led to the increased production of ajmalicine ; in Ophiorrhiza pumila , the anti‐cancer camptothecin was significantly improved by overexpressing geraniol‐10‐hydroxylase and strictosidine synthase ; in Salvia miltiorrhiza , biosynthesis of tanshinone was enhanced by different combination of the key enzymes . These cases strongly suggest that overexpression of key enzymes is a very potent tool for genetic improvement of metabolite biosynthesis.…”
Section: Resultsmentioning
confidence: 99%
“…There are a lot of successful cases in this field. In A. belladonna and A. acutangulus , biosynthesis of scopolamine was dramatically enhanced by overexpressing the committed enzymes, H6H and TRI in A. annua , the production of artemisinin was greatly promoted by overexpressing CYP71AV1 and aldehyde 11Δ(13) reductase ; in Catharanthus roseus , overexpressing strictosidine synthase led to the increased production of ajmalicine ; in Ophiorrhiza pumila , the anti‐cancer camptothecin was significantly improved by overexpressing geraniol‐10‐hydroxylase and strictosidine synthase ; in Salvia miltiorrhiza , biosynthesis of tanshinone was enhanced by different combination of the key enzymes . These cases strongly suggest that overexpression of key enzymes is a very potent tool for genetic improvement of metabolite biosynthesis.…”
Section: Resultsmentioning
confidence: 99%
“…Gene encoding STR has been cloned and characterized from hairy root cultures of Ophiorrhiza pumila (Yamazaki et al, 2003). Although much of the information regarding the steps in-between strictosidine and camptothecin is not available, Cui et al (2015) reported that the co-overexpression of geraniol-10-hydroxylase and strictosidine synthase increased camptothecin accumulation in O. pumila hairy root cultures.…”
Section: Screening For Bioactive Compoundsmentioning
confidence: 99%
“…In plants such as Catharanthus roseus , geraniol hydroxylation is catalyzed by CYP76B6. However, the low activity or expression level of CYP76B6 introduced in engineered recombinant microorganisms seem to be the bottlenecks in strictosidine synthesis . Brown et al.…”
Section: Discussionmentioning
confidence: 99%